Utrata języka. Próba empatycznej lektury patografii osób po udarach mózgu - Okupnik, Małgorzata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
Source literature uses the term pathography to define a text about suffering and illness written from a patient’s perspective. There are three purposes of pathographies: they allow their authors to make their lives more coherent, i.e. continuous and meaningful, they help them understand what their bodies experienced during illness, and they make them discover how to stimulate the body to deal with its effects. There is a specific type of pathographies written by stroke survivors. The effects of a stroke include paresis of the body and aphasia which never fully disappear. Patients talk of the loss of previous identity or a transformation caused by the illness.